Antifungal immunity mediated by C-type lectin receptors may be a novel target in immunotherapy for urothelial bladder cancer - Li, Tianhang; Liu, Tianyao; Zhao, Zihan; Pan, Yuchen; Xu, Xinyan; Zhang, Yulin; Zhan, Shoubin; Zhou, Shengkai; Zhu, Wenjie; Guo, Hongqian; Yang, Rong (Frontiers in Immunology, 2022)
Immunotherapies, such as immune-checkpoint blockade and adoptive T-cell therapy, offer novel treatment options with good efficacy for patients with urothelial bladder cancer. However, heterogeneity and therapeutic resistance have limited the use of immunotherapy. Further research into immune-regulatory mechanisms in bladder cancer is urgently required. Emerging evidence demonstrates that the commensal microbiota and its interactions with host immunity play pivotal roles in a variety of physiological and pathological processes, including in cancer. The gut microbiota has been identified as a potentially effective target of treatment that can be synergized with immunotherapy. The urothelial tract is also a key site for multiple microbes, although the immune-regulatory role of the urinary microbiome in the process of carcinogenesis of bladder cancer remains to be elucidated. We performed a comprehensive analysis of the expression and biological functions of C-type lectin receptors (CLRs), which have been recognized as innate pathogen-associated receptors for fungal microbiota, in bladder cancer. In line with previous research on fungal colonization of the urothelial tract, we found that CLRs, including Dectin-1, Dectin-2, Dectin-3, and macrophage-inducible Ca2+-dependent lectin receptor (Mincle), had a significant association with immune infiltration in bladder cancer. Multiple innate and adaptive pathways are positively correlated with the upregulation of CLRs. In addition, we found a significant correlation between the expression of CLRs and a range of immune-checkpoint proteins in bladder cancer. Based on previous studies and our findings, we hypothesize that the urinary mycobiome plays a key role in the pathogenesis of bladder cancer and call for more research on CLR-mediated anti-fungal immunity against bladder cancer as a novel target for immunotherapy in urothelial bladder cancer.